n - 9; 9 (b, 2010)
Collection of speeches of Sheikh Mujibur Rahman, 1922-1975, politician and former president of Bangladesh.
Keywords: Mujibur Rahman, -- Sheikh, -- 1920-1975 -- Political and social views; Bangladesh -- Politics and government